Tissue and cellular phosphorus storage during development of phosphorus toxicity in Hakea prostrata (Proteaceae) - Shane, Michael W (Journal of experimental botany, 2004)
Storage of phosphorus (P) in stem tissue is important in Mediterranean Proteaceae, because proteoid root growth and P uptake is greatest during winter, whereas shoot growth occurs mostly in summer. This has prompted the present investigation of the P distribution amongst roots, stems, and leaves of Hakea prostrata R.Br. (Proteaceae) when grown in nutrient solutions at ten P-supply rates. Glasshouse experiments were carried out during both winter and summer months. For plants grown in the low-P range (0, 0.3, 1.2, 3.0, or 6.0 micromol d(-1)) the root [P] was > stem and leaf [P]. In contrast, leaf [P] > stem and root [P] for plants grown in the high-P range (6.0, 30, 60, 150, or 300 micromol P d(-1)). At the highest P-supply rates, the capacity for P storage in stems and roots appears to have been exceeded, and leaf [P] thereafter increased dramatically to approximately 10 mg P g(-1) dry mass. This high leaf [P] was coincident with foliar symptoms of P toxicity which were similar to those described for many other species, including non-Proteaceae. The published values (tissue [P]) at which P toxicity occurs in a range of species are summarized. X-ray microanalysis of frozen, full-hydrated leaves revealed that the [P] in vacuoles of epidermal, palisade and bundle-sheath cells were in the mM range when plants were grown at low P-supply, even though very low leaf [P] was measured in bulk leaf samples. At higher P-supply rates, P accumulated in vacuoles of palisade cells which were associated with decreased photosynthetic rates